Bleeding Meckel’s Diverticulum in an Infant - A Case Report - Shrestha, MK; Gurubacharya, RL; Devkota, K; Agarwal, N (Journal of Nepal Paediatric Society, 2014)
Meckel’s diverticulum is a congenital diverticulum. Mostly it is asymptomatic. In children the commonest complication is lower GI bleeding. High index of suspicion is required for its diagnosis. Technetium-99m pertechnetate scan is useful to detect ectopic gastric mucosa. Surgical treatment of symptomatic Meckel’s diverticulum is diverticulectomy or ileal resection. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9523 J Nepal Paediatr Soc 2014;34(1):54-56